Pendidikan Islam Berwawasan Multikultural - Alam, Masnur; Daflizar, Daflizar (BELAJEA: Jurnal Pendidikan Islam, 2018)
Which is prone to cause conflict, thus State Islamic Institute of Kerincias one of the stateuniversities feels obliged to include multicultural courses into its curriculum.The purpose of this study was to know the implementation of "Islamic Education with Multicultural Insights" at the State Islamic Institute ofKerinci. This research was a field research study, with the qualitative type. The main instruments were observation, in-depth interviews, and documentation. The findings of the study are: That the State Islamic Institute ofKerincihas implemented Islamic education with multicultural insights through the lecture process, beginning with designing a syllabus that contains the strengthening of the theory, that God has created cultural diversity which is sunnatullah, rahmat, assets, strength, unifying tool that must be appreciated and thankful for, and that cultural diversity, peace and harmony have received a positive response from the students that they canapply in their daily life and even they are be able to be a massive pioneer in creating peace and harmony in society